CHANGES IN ECONOMIC STRUCTURE AND THEIR EFFECT ON POVERTY IN MALUKU PROVINCE - Fibryano Saptenno; Janni Effendi; Muh Ridhwan Assel (Jurnal Cita Ekonomika, 2021)
The indicators used to measure changes in economic structure and their effect on poverty are the Primary Sector Growth Factor (GR), Secondary Sector Growth (GS), and Tertiary Sector Growth (GT) are factors that affect Economic Structure Change (YR, YS, YT ), Per capita Income, and Poverty Level. So far, Maluku Province is still attached to a poor province. This study aims to analyze changes in economic structure and their effect on poverty in Maluku Province for the 2009-2018 period. The data collection method in this study uses documentation techniques. While the data analysis technique to determine the economic structure uses Location Quetient (LQ) analysis and Shift Share analysis. Meanwhile, to measure the influence of the economic structure on the poverty level, it is carried out through a two-stage analysis. The first stage is to directly analyze the effect of the economic structure on the poverty level, then the second stage is to analyze the effect of the economic structure on the poverty level through the absorption of labor. The analytical technique used is Path Analytic technique. Based on the results of the study (1) From the Shift Share analysis of the Gross Regional Domestic Product (GRDP) of Maluku Province in 2009-2018, it shows that the economic structure in Maluku Province is dominated by the primary sector, as seen from the total component of the Shift Share analysis of the nine sectors, there are The three sectors that contribute the most to GRDP are agriculture, construction, and services. While the results of the Shift Share analysis on the employment of Maluku Province in 2009-2018, the primary sector has a negative Shift Share component value of -31775 workers, which is slower to absorb labor than the same sector at the provincial level. The results of data analysis through Path Analysis show that (2) the economic structure contributes and has a significant effect on employment as much as 55%; (3) The economic structure contributes directly and has a significant effect on the poverty rate by 40%.